DNA barcoding and morphological observations of three lichenized fungal species from James Ross Island (Antarctic Peninsula) - M. G. Halıcı; M. Kahraman (Ukrainian Antarctic Journal, 2021)
Antarctica seems to many people to be a very remote, isolated, and mysterious place at the end of the world, and its name is hardly mentioned in normal life and conversation. However, considering that it plays a key role in the rapidly warming global climate system and its contribution to the continuing sea-level rise, its importance today is increasing day by day and it can be seen that it is of vital importance for humanity. There is increasing interest in the distribution of terrestrial organisms in Antarctica because of the potential use of biodiversity as a predictor or indicator of climate change. Lichenized fungi cover large areas of Antarctica that are not covered by ice and form precursor organisms that thrive in harsh environments. They are the largest contributors to biomass and diversity. The characteristic features of these organisms can be counted as developing certain protective mechanisms, adapting to temperature and radiation, and surviving even when the amount of water in their body is minimized. On the other hand, lichenized fungi are the most dominant components of Antarctic terrestrial vegetation, and their adaptation to extreme conditions; growth forms, reproduction, adaptation to environmental conditions can also be explained through mechanisms. Because of the lichens, dominant organisms of Antarctica, studying lichen biodiversity is very important. Although around 500 species of lichens were reported from Antarctica, the lichen biodiversity of the continent is far from being fully known; as in the last 5 years of our studies on Antarctic lichens, we and other scientists reported a significant number of undescribed or unreported species. So the lichen biodiversity of Antarctica is not fully known as there are still many undescribed or unreported species on the continent. In this paper, we deal with three lichenized fungal species: Arthonia glebosa Tuck., Lecanora atromarginata (H. Magn.) Hertel & Rambold and Lecidea tessellata Flörke which are common in James Ross Island, using nrITS, mtSSU, and RPB1 sequences. The lichen samples are studied by morphological and anatomical characters. Inaddition, to determine the phylogenetic positions of the species, we provide nrITS and mtSSU of these 3 species from Antarctica and additionally RPB1 sequences of Lecidea tessellata.